Translating 2 John 12 and 3 John 14. Issue 3 (December 2020) - Beasley, C. M.
This paper explores the background of the phrase stoma pros stoma as it occurs in 2 John 12 and 3 John 14. If John drew from Num 12.8 and the "Prophet like Moses" theme in the Pentateuch when writing this phrase, then it may have not only rhetorical, but also theological significance in these letters. A translation of this phrase is offered that maintains John's connection to the Septuagint and remains sensitive to the context of the letter closings.